Gambaran Resiliensi Mahasiswa Broken Home (Indo-MathEdu Intellectuals Journal, 2025)
Students who are victims of broken homes are often in difficulties in emotional development, personality and socialization to the environment. Students also experience emotional instability, become lazy, moody and want to be noticed from outsiders. This study aims to find out the picture of the resilience of broken home students. The research uses a type of qualitative research with a phenomenological approach. The data collection technique of this research is using observation, interview and documentation techniques. There are three students who have experienced broken homes with an age range of 22-23 years. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the data analysis showed that students living in broken homes in Bukittinggi City felt a lot of internal and external pressure which caused them to often feel excessive stress and changes in the emotional atmosphere felt without the help or guidance of their parents. Students often feel insecure and unconfident when meeting their friends who have harmonious families. The past experience left behind by her father makes her feel unneeded and loved by others. After a divorce, not only are they emotionally troubled but they also have to go through economic hardships that trigger other psychological problems.